Cardiovascular safety of febuxostat versus allopurinol among the Asian patients with or without gout: A systematic review and meta‐analysis - Jian‐hao Deng; Peng‐hui Lai; Li‐shan Xie; Shu‐sheng Qiu; De‐sheng Qiu; Jia‐xing Zhang (Wiley, 2024)
Abstract The cardiovascular (CV) safety of febuxostat compared to allopurinol for the treatment of hyperuricemia among Asian patients is uncertain. In this study, we conducted a systematic review and meta‐analysis to compare the CV safety profiles of febuxostat with allopurinol in Asian patients with hyperuricemia. A total of 13 studies were included. On the basis of the pooled results of cohort studies, febuxostat users were at a significantly higher risk for acute coronary syndrome (ACS; hazard ratio [HR]: 1.06, 95% confidence interval [CI]: 1.03-1.09, p < 0.01), atrial fibrillation (HR: 1.19, 95% CI: 1.05-1.35, p < 0.01) than allopurinol users, whereas no significant difference between febuxostat and allopurinol existed for urgent coronary revascularization (HR: 1.07, 95% CI: 0.98-1.16, p = 0.13), and stroke (HR: 0.96, 95% CI: 0.91-1.01, p = 0.13). Nevertheless, that difference in results of acute decompensated heart failure (ADHF; HR: 0.73, 95% CI: 0.35-1.53, p = 0.40) and all‐cause death (HR = 0.86, 95% CI: 0.49-1.51, p = 0.60) was not significant based on randomized controlled trials. In the Chinese subgroup, febuxostat could increase the risk of ADHF (HR: 1.22, 95% CI: 1.01-1.48, p < 0.05), CV death (HR: 1.25, 95% CI: 1.03-1.50, p < 0.05), and all‐cause mortality (HR: 1.07, 95% CI: 1.01-1.14, p < 0.05) compared to allopurinol. In conclusion, the use of febuxostat, compared with allopurinol among Asian patients, was associated with a significantly increased risk of adverse CV events.